Utilization of a scoring system for diagnosis of chronic lymphocytic leukemia in Thai patients. - Orathai Promsuwicha (2018)
Chronic lymphocytic leukemia (CLL) is a rare B-lymphoid malignancy in Southeast Asia. We evaluated whether a scoring system based on the expression of CDS, CD23, FMC7, CD79b and surface immunoglobulin (Slg) could be utilized to distinguish CLL from other types of lymphoid neoplasms in the Thais. One-hundred and forty-five samples with a clinical suspicion for CLL were analysed by flow cytometry. A score of one was assigned if the following marker was identified: CD5+, CD23+, FMC7-, CD79b- and SIg(-/weak). A cut-off score of > or =3 was required for the definitive diagnosis of B-CLL. Only 50 cases (34.5%) were confirmed as B-CLL (scores > or =3). Cases with scores > or =3 had significantly higher leukocyte counts and marrow/blood lymphocytes than cases with scores < or =2. Dual CD5/CD23 expression was found in 87.5% of CLL cases. In 81 cases with scores < or =2, a variety of non-CLL disorders predominated, such as marginal zone lymphoma, splenic lymphoma with villous lymphocytes, mantle cell lymphoma, and prolymphocytic leukemia. A score of 3 and dual CD5/CD23 expression are essential for the diagnosis of CLL while a score of 2 mostly indicative of non-CLL. The majority of clinical cases of CLL turned out to be non-CLL by flow cytometry. Increased utilization of this scoring system should increase the accuracy of diagnosis of this rare type of leukemia in the Thai population.